IMPROVING STUDENTS READING COMPREHENSION ON NARRATIVE TEXT THROUGH GROUP WORK - Septianingsih, Rina; Susilawati, Endang; Salam, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research is to investigate how well Group work technique can improve students’ reading comprehension to the eight grade students of MTs Al Muhajirin.To collect the data, the writer used comprehension test, observation checklist table, and field notes. The treatments took two cycles. The participant of this research is the students in eight grade students especially class VIII of MTs Al Muhajirin Rasau Jaya in academic 2014/2015, which consist of 22 students.Based on the achievement test’s result, the researcher discovered a good mark that was shown by the scores of the students from cycle to cycle was increases. The mean score of the first cycle was 61.36 and the second cycle was 71.81.The research findings of the classroom action research were satisfying. All the indicators of success had been fulfilled. Students’ mean score increased and teaching learning process become better. Group Work helps students in understanding the text. Keywords:reading comprehension, narrative text, group work Abstrak: tujuanpenelitianiniadalahuntukmengetahuiseberapabaikteknikkerjakelompokdapatmeningkatkanpemahamanmembacasiswakelas 8 MTs Al Muhajirin. Dalammengumpulkan data, penulismenggunakanujipemahaman, table observasi, dancatatanlapangan.Penelitiandilakukandalam 2 siklus.Objekpenelitiannyaadalahsiswakelas 8 MTs Al MuhajirinRasau Jaya padatahunpelajaran 2014/2015, yang terdiriatas 22 siswa.Berdasarkanhasilujikemampuan, penelitimenemukanbahwanilai yang baikditemukanmeningkatdarisiklus yang satukesiklusberikutnya.Nilai rata – rata padasikluspertamaadalah 61.36 danpadasikluskedua 71.81.Temuanpadapenelitianinihasilnyamemuaskan.Semuaindikatorkeberhasilansiswadapatterpenuhi.Nilai rata – rata siswameningkatdan proses pembelajaran pun menjadilebihbaik. Kerjakelompokmembantusiswadalammemahamiteks. Kata Kunci: pemahamanmembaca, teksnaratif, kerjakelompok